Software in Ireland: A Balance of Entrepreneurship and… Lifestyle Management. - Cusumano, Michael A. (Communications of the ACM, 2005)
Presents the author's views on the recent success of the Irish software industry. View that Ireland, predating India and China, has been a major success story for encouraging development of the software business and high-technology export businesses; Assets that make Ireland a great launching point for overseas companies; Adroitness of the local software entrepreneurs.